Architecture of the soluble receptor Aer2 indicates an in-line mechanism for PAS and HAMP domain signaling - Airola, Michael V. (2012)
Bacterial receptors typically contain modular architectures with distinct functional domains that combine to send signals in response to stimuli. Although the properties of individual components have been investigated in many contexts, there is little information about how diverse sets of modules work together in full-length receptors. Here we investigate the architecture of Aer2, a soluble gas-sensing receptor that has emerged as a model for PAS and poly-HAMP domain signaling. The crystal structure of the heme-binding PAS domain in the ferric, ligand-free form, in comparison to the previously determined cyanide-bound state, identifies conformational changes induced by ligand binding that are likely essential for the signaling mechanism. Heme-pocket alternations share some similarities with the heme-based PAS sensors FixL and EcDOS, but propagate to the Iβ-strand in a manner predicted to alter PAS-PAS associations and the downstream HAMP junction within full-length Aer2. SAXS of PAS and poly-HAMP domain fragments of increasing complexity allow unambiguous domain assignments and reveal a linear quaternary structure. The Aer2 PAS dimeric crystal structure fits well within ab initioSAXS molecular envelopes and pulsed-dipolar ESR measurements of inter-PAS distances confirm the crystallographic PAS arrangement within Aer2. Spectroscopic and pull-down assays fail to detect direct interactions between the PAS and HAMP domains. Overall, the Aer2 signaling mechanism differs from the E. coliAer paradigm, where side-on PAS-HAMP contacts are key. We propose an in-line model for Aer2 signaling, where ligand binding induces alterations in PAS domain structure and subunit association that is relayed through the poly-HAMP junction to downstream domains.